Echoing the English Language Experiences of Multilingual Students in Formal and Informal Settings (Asia Pacific Journal of Social and Behavioral Sciences, 2022)
The present study investigates the factors that influenced the English language learning/acquisition of nine multilingual university students who majored in English. Using the qualitative descriptive design and Sim’s categories of English language learning factors, the participants narrated their formal and informal English language experiences through a summative diary and informal interview. In general, the results show the same set of key categories that are found in previous studies i.e., motivation, beliefs, autonomy, anxiety, language learning strategies, and instructional materials, activities, and facilities. However, the collection of specific narrations paints a different picture of these multilingual participants’ English language learning experiences. Based on the results, recommendations are given to enhance the teaching and learning of English in multilingual and multicultural settings and the context of the present study. It is advised to use multilingual and multicultural approaches that assist English learning and acquisition both within and outside of the classroom.
Keywords: language learning and acquisition, summative diary, factors influencing English language learning, multilingual students